Функціональний розклад вільної енергії як узагальнений підхід до рівняння стану густих флюїдів - Bardik, V.Yu.; Nerukh, D.; Pavlov, E.V.; Vlasyuk, M.S. (Publishing house "Academperiodika", 2012)
A version of the thermodynamic perturbation theory based on a scaling transformation of the partition function has been applied to the statistical derivation of the equation of state in a high-pressure region. Two modifications of the equations of state have been obtained on the basis of the free energy functional perturbation series. The comparative analysis of the experimental PVT-data on the isothermal compression for the supercritical fluids of inert gases has been carried out.